Податкове стимулювання інноваційної діяльності в системі державного регулювання - Васільєва, Леся Миколаївна; Vasilieva, Lesia (Товариство з обмеженою відповідальністю "Видавничий дім "Гельветика", 2019)
Уточнена сутність податкового стимулювання інноваційної діяльності на рівні держави виходячи з цільового призначення (виступати спонукальною причиною до здійснення суб'єктами господарювання інноваційної діяльності в рамках чинного податкового законодавства) і механізму дії (забезпечувати зниження податкового навантаження та вивільнення фінансових ресурсів для здійснення витрат інноваційного характеру), податкових стимулів, які лежать в її основі, що розвиває теоретичні аспекти податкового стимульований та інноваційної діяльності. Узагальнено класифікацію методів та інструментів, що застосовуються в податковому стимулюванні інноваційної діяльності. Визначено основні напрями розвитку податкового стимулювання інноваційної діяльності. It was established that the support of innovation activity, including through its tax incentives, was determined by the goal of the economic policy of Ukraine at the present stage. Among the fnancial mechanisms of state stimulation of the economy (budget, foreign economic, insurance, leasing, etc.), tax incentives were the most widespread. The essence of tax stimulation of innovation activity at the state level based on the intended purpose (to act as a motive reason for the implementation by business entities of innovation activities within the framework of the current tax legislation) and the mechanism of action (to ensure reduction of the tax burden and the release of fnancial resources for the implementation of expenses of an innovative nature) is clarifed. the tax incentives that underlie it, which develops the theoretical aspects of tax incentives and innovation activities and. It is noted that the development of a stimulating function of taxes is an important factor not only in strengthening fnancial stability of enterprises, growth of investment activity of branches of economy, increase of rates of social and economic development, introduction of new technologies, development of new technological methods, but also increase of tax revenues of the state. Increasing fscal revenues from tax incentives for innovation is one of the most important ways of diversifying tax revenues and strengthening the fnancial position of the state. A general classifcation of methods and tools used in tax incentives for innovation. All methods of tax incentives for innovation activity differ in content, focus and strength of infuence, but have the sole purpose, namely obtaining signifcant results for the economy in this feld of economic relations. From how well the methods of tax incentives for innovation are successfully implemented, one can argue about the effectiveness of the tax system as a whole. The basic directions of development of tax incentives of innovative activity are determined.
Tax distribution of innovative activities in the state regulation system
Keywords: інновації; innovation; інвестиції; investment; інноваційна діяльність; innovation activity; податкові інструменти; tax instruments; податкове стимулювання.; tax incentives